Hari raya classics - Marina Mustafa 1965- (MPH masterclass kitchens, 2015)
Though bred in Johor, Marina has accumulated a wealth of recipes from across Peninsular Malaysia and beyond, some of which appears in this book for your own Raya celebration. To accompany your lemang, ketupat palas or nasi impit (how about all three?), there's a selection of rendang, as well as pungent tasty condiments such as kuah kacang, serunding ikan and sambal goreng Johor. There's also a la carte dishes that include soto ayam, nasi dagang and lodeh. Wrap up the meal with sweets such as semperit, batang buruk or kuih bangkit. Also, find out what Hari Raya means to Marina, what Raya was like during her childhood and how the occasion has evolved since then.